Novel Supramolecular Assemblies of Co(III) & Cu(II) with Diethylenetriamine and Azide: Synthesis, Structure, Spectroscopic and Magnetic Studies. Issue 8 (22nd February 2018) - Pandey, Priyanka; Cosquer, Goulven; Yamashita, Masahiro; Sunkari, Sailaja S.
Abstract: In exploring the role of increased ligand basicity as well as denticity on moving from ethylenediamine (en) or 1, 3‐diaminopropane (1, 3‐dap), on supramolecular solid formation, complexation involving diethylenetriamine (det) and azide with Co II and Cu II afforded three new complexes [Co(det)2 ](N3 )3 (1), [Co(det)(N3 )3 ](2) and [Cu2 (det)2 (N3 )5 (H2 O)2 Na](3) under self assembling conditions and are characterized structurally and magnetically. Formation of1 and2 is sensitive to temperature of crystallization, while such a temperature influence could not be observed for Cu II system due to lack of crystals at low temperatures. As expected with a tridentate ligand, strong chelation stabilizes1 at LT and is a thermodynamically stable product, while isolation of2 at RT conditions is under kinetic control. Decomposition of2 at high temperatures (above 70 °C) as revealed through temperature dependent UV‐vis spectral studies also confirms its instability. Presence of three donor sites of det, leads to interesting structural pattern in Jahn‐Teller active Cu II, resulting in cationic chains of [Cu(det)(N3 )]n + bridged by μ‐1, 3 azido bridges to the neighboring [Na(H2 O)2 (N3 )2 ] − units, thus leading to a 2‐D assembly of alternating layers of cationic and anionic chains in the unit cell of3 . Magnetic studies of3 reveals anti‐ferromagnetic interaction between the copper ions (J=– 0.479 cm –1 ), in conformity with the bridge angle dependent magnetic behavior in azido bridged copper complexes. Abstract : Changing the amine from chelating bidentate (en and dap) to more basic tridentate det, resulted in complexes1, 2 and 3. Crystallisation temperature controls the formation of1 and2 having completely different structures.3 consists of alternating cationic and anionic chains of [Cu(det)(N3 )]n + and [Na(H2 O)2 (N3 )2 ] − units, bridged by μ‐1, 3 azido bridges and exhibits weak antiferromagnetic interactions ( J =– 0.479 cm –1 )..